Awareness, willingness and barriers to HIV Self-testing (HIVST) among Men who Have Sex with Men (MSM) in Brazil, Mexico, and Peru: A web-based cross-sectional study - Oliver A. Elorreaga; Thiago S. Torres; E. Hamid Vega-Ramirez; Kelika A. Konda; Brenda Hoagland; Marcos Benedetti; Cristina Pimenta; Dulce Diaz-Sosa; Rebeca Robles-Garcia; Beatriz Grinsztejn; Carlos F. Caceres; Valdilea G. Veloso (Public Library of Science (PLoS), 2022)
HIV self-testing (HIVST) is an essential tool within the combined HIV prevention package and has been available in Latin America since 2015. However, HIVST use among key populations remains low. This study describes awareness, willingness, and barriers to HIVST among MSM in Brazil, Mexico, and Peru. A cross-sectional web-based survey was advertised in two geosocial networking apps (Grindr and Hornet) and Facebook in 2018. We included cisgender men ≥18 years old who self-reported HIV-negative status. We used multivariable Poisson regression models to calculate adjusted prevalence ratios (aPR) to assess the factors associated with willingness to use HIVST for each country. A total of 18,916 completed the survey, 59% from Brazil, 30% from Mexico, and 11% from Peru. Overall, 20% of MSM had never tested for HIV. Awareness and willingness to use HIVST were higher in Brazil than in Peru and Mexico (p < .001). Across the countries, the patterns of association of willingness with HIVST barriers were similar. Most participants think post-test counseling is essential and that dealing with a positive result would be difficult (aPR 1.13 to 1.37, range of aPRs across the three countries). Having the knowledge to deal with a positive HIVST resulted in increased willingness to use HIVST (aPR range: 1.11 to 1.22), while a lack of trust in HIVST compared to HIV testing in clinics was inversely associated (aPR range: 0.80 to 0.90). In general, willingness to use HIVST was associated with higher income (aPR range: 1.49 to 1.97), higher education (aPR range: 1.13 to 1.42), and willingness to use PrEP (aPR range: 1.19 to 1.72). Efforts to increase HIVST knowledge and resolve perceived barriers are warranted, especially among MSM with lower income and education from Brazil, Mexico, and Peru. Personalized virtual counseling could be crucial among this population. In addition, those willing to use HIVST are also willing to use PrEP. It indicates that HIVST delivery could be incorporated into PrEP programs within the Brazilian Public Health System and eventually in Mexico and Peru.